Navigational intelligence at river: a laser-based imaging approach for nocturnal vessel detection - Zafreen, Zasia; Fazal, Mehnaz Ara; Maisha, Umaiya Ahmed; Salem, Mohammed Sadeq; Sajin, Mehrab Hossain (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.